2012
DOI: 10.1108/14769011211202283
|View full text |Cite
|
Sign up to set email alerts
|

Relationships, learning and team working in UK services for children

Abstract: Purpose -This paper seeks to report on education, health, and social care practitioners' experiences of working across traditional boundaries and establishing new relationships in the context of the Common Assessment Framework (CAF) in UK children's services. Design/methodology/approach -Semi-structured interviews were conducted with a total of 20 education, health and social care practitioners, and operational managers using the qualitative methodology of interpretative phenomenological analysis. Findings -Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…One of the main facilitators appeared to be the synchronous one-time collaboration instead of the traditional asynchronous circulation of patient information among providers. [28][29][30] Synergistic interactions improved communication and promoted the development of trust and mutual respect. In this way, the TIP Program overcomes important barriers described in the literature [13][14][15] through understanding each other's roles and responsibilities, and timely and appropriate communication.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main facilitators appeared to be the synchronous one-time collaboration instead of the traditional asynchronous circulation of patient information among providers. [28][29][30] Synergistic interactions improved communication and promoted the development of trust and mutual respect. In this way, the TIP Program overcomes important barriers described in the literature [13][14][15] through understanding each other's roles and responsibilities, and timely and appropriate communication.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-agency collaboration can have extremely positive outcomes for victims and survivors if they are done well (Robinson et al, 2008). While much of the research in this area comes from the US and the UK (see Collins & McCray, 2012;Garret, 2004;Houghton, 2011; research for Canada. Robinson et al (2008) explain that multi-agency relationships are the cornerstone to victim programming and have been a priority for the UK government for years.…”
Section: Benefits To Collaborationmentioning
confidence: 99%
“…2012interviewed frontline practitioners and managers in education, health and social care, and found that overall, relationships improved when they implemented a multi-agency collaboration. The team improved in terms of communication and planning though this process was gradual and not without tensions (Collins & McCray, 2012).…”
Section: Benefits To Collaborationmentioning
confidence: 99%
See 2 more Smart Citations